Peningkatan Literasi Kebencanaan untuk Optimalisasi Informasi Peringatan Dini Bencana Geo-Hidrometeorologi - Munawar, Munawar; Haryanto, Yosafat Donni; Abigael, Febby Debora; Muftareza, Arfany Dimas; Muthahhari, Ilham; Mardiyansyah, Adji; Sinambela, Marzuki (Forum Kerjasama Pendidikan Tinggi, 2026)
Tangerang City is one of the regions in Banten Province that is vulnerable to geo-hydrometeorological disasters and has a relatively large population with rapid urban growth, which can increase the risk of such disasters. Therefore, information, understanding, and actions regarding geo-hydrometeorological disasters are required. Environmental damage and land use change, such as deforestation, urbanization, river sedimentation, and land function conversion, are significant issues. This activity aims to enhance disaster literacy based on Meteorology, Climatology, Geophysics, and Instrumentation (MKGI) in Tangerang City, scheduled for Monday, July 21, 2025, at SMA Al-Husna, Tangerang City, with a total of 67 participants. Through interactive methods that include material presentation, question and answer sessions, quizzes, and questionnaire filling, participants are provided with a comprehensive understanding of geo-hydrometeorological disasters, mitigation strategies, and the utilization of technology in early warning systems. One of the innovations of this activity is the development of a weather forecast information product based on Telegram bot for the area of Tanah Tinggi Village, which provides weather forecast information automatically using open data from BMKG. Evaluation results show that participants had a good understanding of the socialization material, especially in the topics of information dissemination and geohydrometeorological disasters. The questionnaire index score reached 87.60%, falling into the category of